Critical roles of sepsis-reshaped fecal virota in attenuating sepsis severity - Chancharoenthana, Wiwat; Sutnu, Nattawut; Visitchanakun, Peerapat; Sawaswong, Vorthon; Chitcharoen, Suwalak; Payungporn, Sunchai; Schuetz, Alexandra; Schultz, Marcus J.; Leelahavanichkul, Asada (Frontiers in Immunology, 2022)
Because studies on all fecal organisms (bacteria, fungi, and viruses) in sepsis are never been explored and bacteriophages during sepsis might be adapted against gut bacteria with possible pathogenicity, cecal ligation and puncture (CLP), a sepsis mouse model, was evaluated. In fecal bacteriome, sepsis increased Bacteroides and Proteobacteria but decreased Firmicutes, while fecal virome demonstrated the increased Podoviridae when compared with sham feces. There was no difference in the fungal microbiome (predominant Ascomycota in both sham and CLP mice) and the abundance of all organisms between sepsis and control groups. Interestingly, the transfers of feces from CLP mice worsened sepsis severity when compared with sham fecal transfers, as evaluated by mortality, renal injury (serum creatinine and histology), liver damage (liver enzyme and histology), spleen apoptosis, serum cytokines, endotoxemia, and bacteremia. In contrast, the transfers of fecal viral particles from sepsis mice, but not from sham mice, attenuated inflammation in CLP sepsis possibly through the decrease in several fecal pathogenic bacteria (such as Proteobacteria, Gammaproteobacteria, and Prevotellaceae) as evaluated by fecal microbiome analysis. Perhaps, the isolation of favorable bacteriophages in sepsis feces, increased abundance ex vivo before the oral administration in a high concentration is beneficial.